The influence of financial literacy, saving behaviour, and financial management on retirement confidence among women working in the Malaysian public sector - Sabri, Mohamad Fazli; Teo, Tze Juen (Canadian Center of Science and Education, 2014)
Awareness of retirement confidence has been found to be low in many people, especially in women. Much of past research has revealed that women consistently perform a poor level of retirement confidence compared to men. This study aims to examine the influence of financial literacy, saving behaviour, and financial management on retirement confidence among women working in the Malaysian public sector. Multi-stage random sampling technique was applied as the sampling technique in this study. 708 respondents participated in this study. This study applied Pearson Correlational analysis to determine the relationship between the variables. The findings reveal that retirement confidence is positively correlated with financial literacy, saving behaviour, and financial management. Furthermore, multiple regression analysis was applied to determine the predictors of retirement confidence. This study concludes that financial literacy, saving behaviour, financial management, and financial status are significant predictors of retirement confidence among working women, with financial management as the major factor contributing towards retirement confidence. The findings of this study have practical implications for financial advisors in helping working women to be more aware of their future retirement life financial needs and to prevent financial crisis in later years.